Stakeholder perceptions of drought resilience using government drought compensation in Thailand - Chengot, Rishma; Goodwin, Daniel; Tanguy, Maliko; Armitage, Rachael; Pardthaisong, Liwa; Jha, Srinidhi; Holman, Ian P.; Rey Vicario, Dolores; Visessri, Supattra; Ekkawatpanit, Chaiwat; Hannaford, Jamie (Elsevier, 2025)
In the context of escalating climate challenges in Southeast Asia, this study investigates the dynamics of disaster budget allocation in Thailand and examines farmers' perceptions of drought compensation, focusing on the Ping catchment situated in the Northwest of the country. The main objective of the study was to gauge stakeholders' awareness and views on government drought compensation and evaluate its effectiveness. Using government budget data, drought indicators, and a comprehensive survey in Chiang Mai and Tak provinces, the study explores correlations between budget allocation, drought indicators, and farmers' experiences. A correlation analysis unveils stronger links between compensation and Vegetation Condition Index (VCI) as compared to Drought Severity Index (DSI), with regional variations and the impact of irrigation practices. Compensation shows positive correlations with drought severity, suggesting support to farmers occurs when they suffer severe crop damage. We investigate drought occurrences and their impacts along with farmer's awareness and experiences of drought compensation schemes to uncover disparities in awareness, application rates, and satisfaction levels, providing insights into farmers' views on compensation effectiveness. The study concludes by proposing policy adjustments, tailored regional approaches, and feedback mechanisms to enhance the effectiveness of drought compensation strategies. Despite limitations in sample size and potential biases, this study contributes valuable insights into the complex dynamics of disaster budget allocation, drought compensation, and farmers' perspectives in Thailand, laying a foundation for refining policies and fostering sustainable agricultural practices amidst increasing climate challenges.
Keywords: 4404 Development Studies; 4406 Human Geography; 44 Human Society; Agricultural droughts; Drought compensation; Thailand; Survey; Drought resilience